Tingkat Stres dengan Binge Eating Disorder pada Remaja di Kelurahan X Jakarta Barat - Maria D Tekege; Rima Berlian Putri; Ricky Riyanto Iksan; Roza Indra Yeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between stress levels and Binge eating Disorder in adolescents in X Village, West Jakarta. The study design used a quantitative analytical approach with a cross-sectional approach. The sample consisted of 55 adolescents selected using a total sampling technique. Data were collected using a stress level questionnaire (adapted from the Perceived Stress Scale) and the Binge eating Scale. Data were analyzed using univariate and bivariate methods using the Chi-Square test. The results showed a significant relationship between stress levels and Binge eating Disorder (p = 0.003). Adolescents with high stress levels were more likely to experience binge eating behavior than adolescents with low stress levels. The conclusion of this study suggests that stress plays a significant role in the development of Binge eating Disorder in adolescents. Nursing interventions focused on stress management need to be developed as an effort to prevent eating disorders in adolescents. Keywords: Adolescents, Binge eating Disorder, Stress.